Applicability of different types of patient records for patient recruitment Systems - Schreiweis, Björn; Bergh, Björn (MEDINFO 2015, 2015)
Europe PMC is an archive of life sciences journal literature., Applicability of different types of Patient Records for Patient Recruitment Systems.